Alloy film anti-scaling device with anti-scaling function and manufacturing method

By using anti-scaling alloy sheets with specific compositions and magnetron sputtering technology to prepare Cr films and anti-scaling alloy films, the problems of ion release control and uneven distribution of micro-batteries in the anti-scaling alloy sheets are solved, improving the anti-scaling effect and service life, and simplifying the maintenance process.

CN121137535APending Publication Date: 2025-12-16ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511167419.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-20
Publication Date
2025-12-16

AI Technical Summary

Technical Problem

The release rate of functional ions from existing anti-scaling alloys is difficult to control, leading to water pollution and reduced anti-scaling performance. Uneven distribution of micro-batteries results in a limited range of action. Traditional anti-scaling alloy sheets have short lifespans and are inconvenient to disassemble and clean.

Method used

A scale-resistant alloy sheet with a specific composition ratio, including Cu, Zn, Ni, Sn, Cr, Fe, and Si, is used to prepare a Cr film and a scale-resistant alloy film by magnetron sputtering. Uniformly arranged through holes are set on the alloy sheet, and vacuum heat treatment is combined to improve the density and corrosion resistance.

Benefits of technology

This improved the anti-scaling effect, extended the service life of the alloy sheet, simplified the disassembly and cleaning process, and reduced production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121137535A_ABST
    Figure CN121137535A_ABST
Patent Text Reader

Abstract

The invention discloses an alloy film anti-scaling device with an anti-scaling function and a manufacturing method. The alloy film anti-scaling device comprises at least two pipeline knots connected in series, a front connector connected with the pipeline knot at the front end and a rear connector connected with the pipeline knot at the rear end. The pipeline joint comprises a round pipe and first annular connecting plates arranged at the two ends of the round pipe. Each of the front joint and the rear joint comprises a second annular connecting plate and a connecting pipe connected with the second annular connecting plate, an anti-scale alloy sheet is arranged between every two adjacent first annular connecting plates, and a plurality of uniformly arranged through holes are formed in each anti-scale alloy sheet; austenitic stainless steel is adopted as a substrate of the anti-scale alloy sheet, and a Cr film and an anti-scale alloy film are deposited on the substrate. The anti-scaling agent has the characteristics of good anti-scaling effect and low use cost.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of scale-resistant alloy, in particular to an alloy thin film scale inhibitor with scale-resistant function and a manufacturing method. BACKGROUND

[0002] In the fields of oil exploitation, power production, ship transportation and industrial water treatment, the scaling on the surface of equipment is a long-standing serious technical problem. The scaling mainly refers to the hard deposits formed by the precipitation and deposition of mineral ions (such as calcium and magnesium ions) in water on the surface of equipment, and the main components are calcium carbonate, calcium sulfate, silicate and other insoluble salts.

[0003] According to statistics, the economic loss caused by mineral scaling in equipment such as boilers, turbines and heat exchangers in industrialized countries is as high as 0.17%-0.25% of the gross domestic product.

[0004] The influence of scaling problem on industrial production mainly reflects in three aspects: first, the scaling layer is formed by the accumulation of insoluble salts with low thermal conductivity, which leads to a serious decline in heat transfer efficiency. In the field of oil exploitation, the scaling on the inner wall of downhole pipeline can cause the heat transfer efficiency to decrease by more than 30%; second, the scaling on the inner wall of pipeline can reduce the flow area and increase the fluid resistance, which can increase the pumping energy consumption and even cause the pipeline to be completely blocked in severe cases; third, the local corrosion (such as under-deposit corrosion) under the scaling layer can accelerate the failure of equipment and shorten the service life of equipment.

[0005] The current scale-resistant alloy application technology has certain defects:

[0006] 1. The release speed of functional ions of the scale-resistant alloy is not easy to control, which leads to the over-high concentration of some ions (Zn 2+ , Pb 2+ ) and causes water pollution and affects the scale-resistant performance.

[0007] 2. Due to the non-uniform structure after melting and the uneven distribution of micro-batteries, the scale-resistant distance is short and the range of action is limited. Moreover, due to the uneven distribution of micro-batteries, the continuity of current release is poor, the service life of the traditional scale-resistant alloy sheet is short, and it needs to be frequently replaced.

[0008] 3. The surface roughness and surface energy of the scale-resistant alloy are too high, which leads to the accumulation of insoluble salts on the scale-resistant alloy, separates the scale-resistant alloy from the water, and cannot play a scale-resistant role, so the service life is shortened. SUMMARY

[0009] The purpose of the present application is to overcome the poor scale-resistant effect, short service life and inconvenience of disassembly and cleaning after use of the scale inhibitor in the prior art, and provide an alloy thin film scale inhibitor with scale-resistant function and a manufacturing method.

[0010] To achieve the above objectives, the present invention adopts the following technical solution:

[0011] An alloy film anti-scaling device with anti-scaling function includes at least two pipe joints connected in series, a front connector connected to the front pipe joint, and a rear connector connected to the rear pipe joint. Each pipe joint includes a circular pipe and first annular connecting plates at both ends of the circular pipe. Both the front and rear connectors include a second annular connecting plate and a connecting pipe connected to the second annular connecting plate. An anti-scaling alloy sheet is provided between adjacent first annular connecting plates, and an anti-scaling alloy sheet is provided between connected first and second annular connecting plates. The anti-scaling alloy sheet has a plurality of uniformly arranged through holes. The anti-scaling alloy sheet includes a circular sheet made of stainless steel, a transition layer on the upper and lower surfaces of the circular sheet, and a functional layer on the outer surface of the transition layer. The transition layer is a Cr film, and the functional layer is an anti-scaling alloy film.

[0012] The alloy film anti-scaling device of the present invention can connect 4-8 pipe joints in series for easy expansion. Adjacent pipe joints are fixedly connected to each other by a first annular connecting plate. The anti-scaling alloy sheet is located between two adjacent first annular connecting plates. An anti-scaling alloy sheet is also provided between the first annular connecting plate and the second annular connecting plate, making it more convenient to disassemble, clean and replace the anti-scaling alloy sheet.

[0013] Preferably, the anti-scaling alloy film is prepared by magnetron sputtering using an anti-scaling alloy target. The mass ratio of each component in the anti-scaling alloy target is as follows: Cu: 1000-1300, Zn: 240-420, Ni: 240-420, Sn: 40-60, Cr: 1-100, Fe: 1-20, Si: 6-10.

[0014] The elements and their contents used in this invention are analyzed as follows:

[0015] With Cu as the substrate, the corrosion products of copper will be deposited on the metal surface to form a corrosion oxide layer. The corrosion oxide layer is uniform but not dense. As corrosion proceeds, the electron transfer path narrows and the product service life increases.

[0016] The Zn standard electrode potential differs from that of copper by 1.1V. During service, the Zn standard electrode is preferentially corroded. 2+ It can inhibit scale formation even at low concentrations by competing with scale-forming cations in water for scale-forming anions.

[0017] The Zn content set in this invention is the optimal content. If the Zn content is higher than 21%, it will increase the smelting cost of the target material, and the zinc content will be difficult to control precisely due to the volatilization of zinc. If the Zn content is lower than 12%, the Zn in the anti-scaling alloy film will be released faster, and the anti-scaling function of the anti-scaling alloy film will be weakened.

[0018] Cu, Zn, and Ni can form a stable Cu-Zn-Ni ternary alloy, which forms a micro-battery with copper. The addition of Ni can control the release of Zn and improve the anti-scaling effect in the anti-scaling alloy film.

[0019] Ni and Zn have a synergistic effect, ensuring the corrosion resistance of the anti-scaling alloy film and controlling Zn release, which is not disclosed in existing technology. If the Ni content is higher than 21%, the Zn release rate will be drastically reduced, resulting in a significant decrease in the anti-scaling effect of the anti-scaling alloy. If the Ni content is lower than 12%, it is difficult to control the release of elements such as Zn and Sn in the anti-scaling alloy film, reducing the corrosion resistance of the anti-scaling alloy film. When hard water flows through the anti-scaling alloy sheet, a large number of ions will dissolve into the hard water, reducing the anti-scaling effect of the anti-scaling alloy.

[0020] Sn can refine grains, improve the wear resistance of alloys, and make alloys more resistant to fluid erosion.

[0021] Cr can promote the formation of a passivation film on Ni and improve its corrosion resistance. During subsequent magnetron sputtering, it can better adhere to the surface of the transition layer. In high-Ni alloys, the addition of Cr can improve the alloy's pitting corrosion resistance.

[0022] The addition of Si is a unique discovery of this invention, as Si can modulate the Zn content. 2+ The release of Zn is more uniform and stable, allowing the anti-scaling alloy to maintain its anti-scaling effect steadily throughout its service life. If the Si content decreases, the Zn release rate increases, significantly reducing the service life of the anti-scaling alloy film, and the excess released Zn... 2+ It will be washed away by the flow of water. If the Si content increases, the release rate of Zn will decrease sharply, and the scale prevention effect of the scale-inhibiting alloy will be significantly reduced.

[0023] In summary, the anti-scaling alloy sheet made from the above-mentioned elements has the advantages of good anti-scaling effect and long service life.

[0024] Preferably, the through hole is a stepped hole, with the diameter of the stepped hole decreasing from top to bottom, and the inner edge of the stepped hole is rounded.

[0025] The rounded corners effectively prevent sharp edges from being preferentially corroded. At the same time, the inlet diameter of the water flow is larger than the outlet diameter, which can accelerate the local water flow rate and significantly reduce scale buildup on the anti-scaling alloy sheet.

[0026] Because when fluid flows through the holes, it can be compared with the fluid velocity and the bulk phase C. b C at the solid-liquid interface i The concentration gradient between them transfers substances to the surface.

[0027] The transfer formula is And k DThe mass transfer coefficient depends on fluid dynamics and channel shape. The lower the surface roughness of the channel and the faster the fluid velocity, the less mass is transferred to the surface of the object.

[0028] From a fluid mechanics perspective, the through-hole structure of this invention ensures that the density of the liquid fluid remains almost unchanged, the internal energy changes minimally, and the local temperature remains almost constant. However, the increased flow velocity significantly accelerates the water pressure, leading to faster fluid velocity and increased shear stress. This makes it easier for scale to be washed away by the water flow, effectively extending the service life of the anti-scaling alloy sheet.

[0029] Preferably, both the first annular connecting plate and the second annular connecting plate are provided with a plurality of corresponding bolt holes, and the corresponding surfaces of adjacent first annular connecting plates are provided with a first annular groove for accommodating the sealing ring, and the corresponding surfaces of the first annular connecting plate and the second annular connecting plate are provided with a second annular groove.

[0030] The corresponding annular connecting plates can be fixedly connected with bolts, which effectively ensures the stability of the connection; the setting of the annular groove and sealing ring gives the alloy film anti-scaling device good sealing performance and avoids water leakage.

[0031] A method for manufacturing an alloy thin-film anti-scaling device with anti-scaling function includes a magnetron sputtering step of anti-scaling alloy sheet:

[0032] Step 5-1: Place the pretreated disc into the sputtering chamber of the magnetron sputtering instrument, fix the disc on the sample stage of the magnetron sputtering instrument, and cover the lower surface of the disc with a mask.

[0033] Step 5-2: Install the Cr target material onto target A, then evacuate the magnetron sputtering chamber and introduce argon gas to sputter a Cr film on the upper surface of the disc to form a Cr film.

[0034] Step 5-3: Power off the magnetron sputtering instrument and stop the argon gas supply to allow the temperature inside the sputtering chamber to drop below 60℃-80℃; remove the Cr target and disc from the sputtering chamber.

[0035] Step 5-4: Repeat steps 5-1 to 5-3, cover the upper surface of the wafer with a mask, and magnetron sputter the lower surface of the wafer;

[0036] Step 5-5: Place the disc into the magnetron sputtering chamber, use a clamp to fix the heated substrate to the disc, install the anti-scaling alloy target onto the B target holder, cover the lower surface of the disc with the sputtered Cr film with a mask plate, sputter the anti-scaling alloy film on the upper surface of the disc with the sputtered Cr film, and remove the disc.

[0037] Steps 5-6: Repeat steps 5-5, cover the upper surface of the disc with a mask, and magnetron sputter an anti-scaling alloy film onto the lower surface of the Cr film.

[0038] Steps 5-7: Place the disc into the heating zone of the furnace tube in the vacuum tube furnace, install insulated furnace plugs at both ends of the furnace tube, and perform vacuum heat treatment to obtain the scale-resistant alloy disc.

[0039] Preferably, the process also includes the preparation step of the anti-scaling alloy target material:

[0040] Step 6-1, Smelting:

[0041] Preheat the graphite crucible to 800±10℃ and hold for 30-45 minutes to remove moisture. Add Cu, Ni, Sn, Cr, Fe, and Si of the anti-scaling alloy target to the graphite crucible according to their mass ratios. Heat the inside of the graphite crucible to 1150℃-1180℃ to completely melt all components. Stir the melt in the graphite crucible electromagnetically for 30-45 minutes. Cool the melt to 1050℃-1080℃ and add zinc ingots to the melt according to the mass ratio of the anti-scaling alloy target. Melt the zinc ingots and stir the melt rapidly with a graphite rod for 10-20 minutes. Cover the melt with a composite flux to prevent surface oxidation. Hold the graphite crucible at 1080℃±10℃ and stir the melt electromagnetically for 8-12 minutes to ensure uniform distribution of the components of the anti-scaling alloy target, thus obtaining the anti-scaling alloy target melt.

[0042] Step 6-2: Deoxidize and refine the molten anti-scaling alloy target material;

[0043] Step 6-3, Pouring:

[0044] Preheat the anti-scaling alloy target mold to 200℃, spray zinc oxide coating on the mold, heat the mold to 1060℃-1100℃, and pour the molten anti-scaling alloy target into the mold under argon protection to obtain the anti-scaling alloy target ingot.

[0045] Step 6-4, Demolding:

[0046] Cool the anti-scaling alloy target mold to 150℃-250℃ for demolding;

[0047] Step 6-5: Homogenize the anti-scaling alloy target ingot through annealing.

[0048] Step 6-6: Hot rolling the anti-scaling alloy target ingot;

[0049] Steps 6-7 involve cold rolling the anti-scaling alloy target material;

[0050] Steps 6-8, Surface treatment and target material processing:

[0051] The cold-rolled anti-scaling alloy target material is surface-machined to a thickness of 4mm, so that the roughness grade of the upper and lower surfaces of the anti-scaling alloy target material reaches N5, thus obtaining the final anti-scaling alloy target material.

[0052] As a preferred option, the sputtering parameters for magnetron sputtering the anti-fouling alloy film are:

[0053] The sputtering chamber was evacuated to a vacuum of 1.0 × 10⁻⁶. -3 Below Pa, the substrate temperature of the sample turntable is raised to 250℃-300℃ through heat transfer from the heated substrate; the bias voltage is adjusted to 100V-120V, argon gas is introduced into the sputtering chamber, and the argon gas flow rate is controlled at 30sccm-40sccm to raise the gas pressure in the sputtering chamber to 0.5Pa-0.7Pa; the voltage of the B target is raised to 300V-400V to perform glow discharge, which ionizes the argon gas and generates argon ions. The argon ions bombard the anti-scaling alloy target, causing the anti-scaling alloy target to sputter; the working gas pressure in the sputtering chamber is adjusted to 0.2±0.1Pa, and pre-sputtering is performed for 5min-10min; after the pre-sputtering process, the voltage and current of the B target are stabilized, the rotation speed of the sample turntable is controlled at 2r / min-4r / min, the voltage and current of the B target are adjusted to achieve a power of 120W-150W, and sputtering is continued for 100min-150min to form an anti-scaling alloy film on the Cr film surface. The anti-scaling alloy film exhibits optimal density and uniformity at a temperature of 280℃ and a power of 135W.

[0054] Preferably, step 5-5 includes the following specific steps:

[0055] Place the disc into the heating zone of the vacuum tube furnace tube, and evacuate the furnace tube to a vacuum level of 1.3 × 10⁻⁶. -3 For pressures below MPa, install insulated furnace plugs at both ends of the furnace tube;

[0056] The temperature inside the vacuum tube furnace is raised to 600℃-800℃ and held for 0.5-2 hours, allowing the disc to cool with the vacuum tube furnace. Once the temperature inside the vacuum tube furnace is below 60℃, the scale-resistant alloy disc is removed.

[0057] After vacuum heat treatment, porosity testing showed that the porosity of the anti-scaling alloy film decreased from 6.7% to 1.3%, with a closed-cell rate of over 85%. Nanoindentation testing indicated that the H / E ratio increased from 0.082 to 0.121 after heat treatment, and the elastic strain capacity increased by 47%, indicating that the mechanical properties of the anti-scaling alloy film were improved after vacuum heat treatment. This also suggests that the density, corrosion resistance, and service life of the anti-scaling alloy film were improved.

[0058] Preferably, the thickness of the Cr film is 200nm-400nm, and the thickness of the anti-scaling alloy film is 1000nm-1200nm.

[0059] The Cr film exhibited good density and uniformity after sputtering at 100W for 25 minutes.

[0060] Through the study of interfacial stress at the thickness of the Cr film, it was found that the thickness range of the Cr film of the present invention can achieve a gradient transition of the thermal expansion coefficient between the anti-fouling alloy sheet and the functional layer. Scratch testing showed that the critical load decreases when the thickness is less than 200 nm, and when it is greater than 400 nm, it leads to the accumulation of growth stress in the functional layer, resulting in an increase in microcrack density. EBSD analysis confirmed that the columnar crystal aspect ratio (110) / (001) of the Cr film is 2.3-2.8, which is significantly improved compared with conventional methods.

[0061] Therefore, the present invention has the following beneficial effects:

[0062] The anti-scaling alloy film consists of columnar crystals oriented along the S110 crystal axis. It has fewer and more orderly grain boundaries, which reduces the scattering of electrons by the grain boundaries. It also has fewer internal defects, which lowers the resistivity and provides more stable current release characteristics. The release rate of scale-prone cations in the columnar crystal film oriented along the S110 crystal axis is controllable. The film composition is more uniform, the surface energy is lower, and the hydrophobicity is better, which can effectively reduce scale adhesion and improve the anti-scaling effect of the anti-scaling alloy sheet.

[0063] The through-hole structure can accelerate the flow rate of local water, significantly reduce scale buildup on the anti-scaling alloy plates, improve the anti-scaling effect, and is easy to disassemble, clean, and replace;

[0064] The anti-scaling alloy sheet uses austenitic stainless steel as a substrate, and deposits a Cr film and an anti-scaling alloy film on the substrate, which can significantly reduce the production cost of traditional anti-scaling sheets. Attached Figure Description

[0065] Figure 1 This is a schematic diagram of the structure of the present invention;

[0066] Figure 2 yes Figure 1 A sectional view;

[0067] Figure 3 This is a schematic diagram of a pipe connection according to the present invention;

[0068] Figure 4 yes Figure 3 A sectional view;

[0069] Figure 5 This is a top view of the anti-scaling alloy sheet of the present invention;

[0070] Figure 6 This is a microscopic morphology diagram of the anti-scaling alloy sheet of the present invention;

[0071] Figure 7 This is a stainless steel hanging plate for preventing scale buildup using traditional anti-scale alloy sheets.

[0072] Figure 8This is a diagram of a stainless steel hanging plate used for scale prevention in Example 1;

[0073] Figure 9 This is a comparison chart of the quality changes of a stainless steel hanging plate obtained by using the anti-scaling alloy sheet of Example 1 and the traditional anti-scaling alloy sheet after anti-scaling treatment.

[0074] Figure 10 This is a comparison chart of pH changes in circulating aqueous solutions obtained after anti-scaling treatment using the anti-scaling alloy sheet of Example 1 and the traditional anti-scaling alloy sheet.

[0075] Figure 11 The Ca content of the circulating aqueous solution obtained after anti-scaling treatment using the anti-scaling alloy sheet of Example 1 and a conventional anti-scaling alloy sheet is... 2+ A comparison chart of concentration changes. Detailed Implementation

[0076] The present invention will now be further described with reference to the accompanying drawings and specific embodiments.

[0077] Example 1

[0078] like Figures 1-5 The embodiment shown is an alloy film anti-scaling device with anti-scaling function, including three pipe joints 1 connected in series, a front connector 2 connected to the front pipe joint, and a rear connector 3 connected to the rear pipe joint; the pipe joint includes a circular pipe 11 and a first annular connecting plate 12 at both ends of the circular pipe; the front connector and the rear connector both include a second annular connecting plate 21 and a connecting pipe 20 connected to the second annular connecting plate, an anti-scaling alloy sheet 4 is provided between adjacent first annular connecting plates, and an anti-scaling alloy sheet is provided between connected first annular connecting plates and second annular connecting plates, the anti-scaling alloy sheet has 19 uniformly arranged through holes 41, the anti-scaling alloy sheet includes a circular sheet made of stainless steel, a transition layer provided on the upper and lower surfaces of the circular sheet, and a functional layer provided on the outer surface of the transition layer; the transition layer is a Cr film, and the functional layer is an anti-scaling alloy film.

[0079] The anti-scaling alloy film was prepared by magnetron sputtering using an anti-scaling alloy target. The mass ratio of each component in the anti-scaling alloy target was: Cu: 1000, Zn: 240, Ni: 420, Sn: 60, Cr: 1, Fe: 20, Si: 10.

[0080] The through hole is a stepped hole, with the diameter of the stepped hole decreasing from top to bottom, and the inner edge of the stepped hole is provided with a rounded corner 411.

[0081] The first annular connecting plate and the second annular connecting plate are each provided with two corresponding bolt holes 121 and anti-scaling alloy sheet receiving grooves 123. The corresponding surfaces of adjacent first annular connecting plates are each provided with first annular grooves 122 for receiving sealing rings, and the corresponding surfaces of the first annular connecting plates and the second annular connecting plates are each provided with second annular grooves 124.

[0082] The anti-scaling alloy sheet in this embodiment is made of 304 austenitic stainless steel, and after purchase, it is machined into the following shape: Figure 5 The shape shown has an outer diameter of The anti-scaling alloy plate has 19 through holes, all with an upper diameter of [missing information]. The lower diameter is The through holes are distributed on the inner, middle and outer rings of the anti-scaling alloy sheet. The center of the inner ring through holes is located at the center of the anti-scaling alloy sheet. The center of the middle ring through holes is 6.5 mm away from the center of the anti-scaling alloy sheet, and the included angle between the centers of the middle ring through holes is 60°. The center of the outer ring through holes is 13 mm away from the center of the anti-scaling alloy sheet, and the included angle between the centers of the middle ring through holes is 30°. The upper and lower edges of all through holes are rounded with a radius R of 0.5 mm.

[0083] A method for manufacturing an alloy thin-film anti-scaling device with anti-scaling function includes a magnetron sputtering step of anti-scaling alloy sheet:

[0084] Step 5-1: Place the pretreated disc into the sputtering chamber of the magnetron sputtering instrument, fix the disc on the sample stage of the magnetron sputtering instrument, and cover the lower surface of the disc with a mask.

[0085] Step 5-2: Place the Cr target material into the sputtering chamber that has been filled with argon gas, install the Cr target material onto target A, and sputter a Cr film on the upper surface of the disc to form a 300nm Cr film.

[0086] The magnetron sputtering Cr target was a commercially available standard material, purchased from Zhongnuo New Materials Technology Co., Ltd., model: 99.95% chromium target, diameter: Thickness: 4mm.

[0087] The steps for magnetron sputtering a Cr film are as follows: The upper and lower surfaces of the 304 stainless steel substrate are progressively ground, followed by mechanical polishing with diamond polishing paste to ensure a smooth, scratch-free surface. The disc is then immersed in a 1:2 acetone-alcohol solution and ultrasonically cleaned for 10 minutes. After cleaning, the disc is removed and dried. The pretreated disc is placed in the sputtering chamber of the magnetron sputtering instrument for fixation and arrangement; the Cr target is fixed to target A within the sputtering chamber. The pretreated disc is placed on the sample turntable within the sputtering chamber, with its upper surface facing down and aligned with the center of target A. The distance between the target and the turntable is 60 mm. The heated substrate is inserted into the back of the turntable, and the disc is secured using clamps. The sputtering chamber is then evacuated to a vacuum of 1.0 × 10⁻⁶. -3 Below Pa; the substrate temperature of the sample turntable is raised to 120℃ by heating the substrate; the bias voltage is adjusted to 90V, argon gas is introduced into the sputtering chamber, the argon gas flow rate is controlled at 20sccm, and the gas pressure in the sputtering chamber is increased to 1.3Pa; the voltage of target A is increased to 350V to perform glow discharge, ionizing the argon gas and generating argon ions, which bombard the Cr target material, causing the target material to sputter; the working gas pressure in the sputtering chamber is adjusted to 0.3±0.2Pa, and pre-sputtering is performed for 10min; after the pre-sputtering process, the voltage and current of target A are stabilized, the rotation speed of the sample turntable is controlled at 3r / min, the voltage and current of target A are adjusted to achieve a power of 100W, and sputtering is continued for 25min to form a Cr film on the upper surface of the wafer, with a thickness of 300nm.

[0088] Step 5-3: Power off the magnetron sputtering instrument and stop the argon gas supply to allow the temperature inside the sputtering chamber to drop below 60℃-80℃; remove the Cr target and disc from the sputtering chamber.

[0089] Step 5-4: Repeat steps 5-1 to 5-3, cover the upper surface of the wafer with a mask, and magnetron sputter the lower surface of the wafer to form a Cr film with a thickness of 300 nm.

[0090] Step 5-5: Place the wafer into the magnetron sputtering chamber, use a clamp to fix the heated substrate to the wafer, install the anti-scaling alloy target onto the B target holder, cover the lower surface of the wafer with the sputtered Cr film with a mask plate, sputter an anti-scaling alloy film of 1100nm on the upper surface of the wafer with the sputtered Cr film, and remove the wafer.

[0091] Steps 5-6: Repeat steps 5-5, cover the upper surface of the disc with a mask, and magnetron sputter an anti-scaling alloy film onto the lower surface of the Cr film.

[0092] Steps 5-7: Place the disc into the heating zone of the vacuum tube furnace tube, and evacuate the vacuum tube furnace tube to a vacuum level of 1.3 × 10⁻⁶. -3 For pressures below MPa, install insulated furnace plugs at both ends of the furnace tube;

[0093] The temperature inside the vacuum tube furnace is raised to 600℃-800℃ and held for 0.5-2 hours, allowing the discs to cool along with the furnace. Once the temperature inside the furnace drops below 60℃, the prepared discs are removed. Figure 5 The anti-scaling alloy sheet shown is illustrated in the following microscopic morphology diagram: Figure 6 As shown.

[0094] The preparation steps of the anti-scaling alloy target material are as follows:

[0095] Step 6-1, Smelting

[0096] Preheat the graphite crucible to 800±10℃ and hold for 30-45 minutes to remove moisture. Add Cu, Ni, Sn, Cr, Fe, and Si of the anti-scaling alloy target material to the graphite crucible according to the mass ratio. Heat the inside of the graphite crucible to 1150℃-1180℃ to completely melt all components. Electromagnetically stir the melt in the graphite crucible for 30-45 minutes. Cool the melt to 1050℃-1080℃. Add zinc ingots to the melt according to the mass ratio of the anti-scaling alloy target material and melt the zinc ingots. Quickly stir the melt with a graphite rod for 10-20 minutes. Cover the melt with a composite flux (20g borax + 10g charcoal) to prevent surface oxidation. Hold the graphite crucible at 1080℃±10℃ and electromagnetically stir the melt for 8-12 minutes to ensure uniform distribution of the components of the anti-scaling alloy target material, thus obtaining the anti-scaling alloy target material melt.

[0097] Step 6-2: Deoxidize and refine the molten anti-scaling alloy target material;

[0098] Add phosphorus copper at a ratio of 5‰ of the scale-inhibiting alloy target material and stir for 3 minutes (reaction: 5Cu2O+2P→P2O5↑+10Cu) to remove dissolved oxygen during smelting and to allow the generated low-melting-point copper phosphate slag to float. Add cryolite refining agent (0.1%), stir, and let stand for 5 minutes to promote the floating of inclusions. Take a sample for rapid analysis. If the difference between the mass fraction of zinc content in the scale-inhibiting alloy target solution and the mass fraction of the designed composition is within 5%, the requirements are met, and proceed to step 6-3. If the difference between the mass fraction of zinc content in the scale-inhibiting alloy target solution and the mass fraction of the designed composition exceeds 5%, zinc ingots need to be added to the scale-inhibiting alloy target solution until the difference between the mass fraction of zinc content in the scale-inhibiting alloy target solution and the mass fraction of the designed composition is within 5%, and proceed to step 6-3.

[0099] Step 6-3, Pouring

[0100] Preheat the anti-scaling alloy target mold to 200℃, spray zinc oxide coating on the mold, heat the mold to 1060℃-1100℃, and pour the molten anti-scaling alloy target into the mold under argon protection to obtain the anti-scaling alloy target ingot; casting parameters: too high temperature will easily oxidize, too low temperature will result in poor fluidity, flow rate 4L / min, after casting, air cool to 500℃ and then water quench to prevent β phase precipitation and embrittlement.

[0101] Step 6-4, Demolding

[0102] Cool the anti-scaling alloy target mold to 200℃ before demolding; prevent the ingot from being completely solidified due to excessive demolding temperature, which may cause deformation or cracking, and prevent the ingot from shrinking and jamming due to excessive demolding temperature, which may increase ejection resistance and damage the mold surface.

[0103] Step 6-5: Homogenize the anti-scaling alloy ingot with annealing.

[0104] The anti-scaling alloy ingot is heated to 650℃ and held for 2 hours, then air-cooled to eliminate ingot segregation and ensure uniform ingot structure.

[0105] Step 6-6: Hot rolling the anti-scaling alloy target ingot;

[0106] The ingot is heated to 780°C and then hot rolled, with each reduction being 15%-20%, until the original thickness is 50% and then hot rolling is stopped.

[0107] Steps 6-7 involve cold rolling the anti-scaling alloy target material;

[0108] The anti-scaling alloy target is cold-rolled, with each reduction controlled at 18%, until it is cold-rolled to 5mm and then stopped.

[0109] Steps 6-8, Surface treatment and target material processing:

[0110] The cold-rolled anti-scaling alloy target material is surface-machined to a thickness of 4mm, achieving a surface roughness grade of N5 on both the upper and lower surfaces. Wire cutting is then used to cut the target material into pieces with a diameter of [missing information]. Target material.

[0111] The sputtering parameters for magnetron sputtering the anti-fouling alloy film are as follows:

[0112] The sputtering chamber was evacuated to a vacuum of 1.0 × 10⁻⁶. -3Below Pa, the substrate temperature of the sample turntable is raised to 280℃ by heating the substrate. The bias voltage is adjusted to 110V, argon gas is introduced into the sputtering chamber, and the argon gas flow rate is controlled at 35sccm to raise the gas pressure in the sputtering chamber to 0.6Pa. The voltage of the B target is raised to 350V to perform glow discharge, which ionizes the argon gas and generates argon ions. The argon ions bombard the anti-scaling alloy target, causing the anti-scaling alloy target to sputter. The working gas pressure in the sputtering chamber is adjusted to 0.2Pa, and pre-sputtering is performed for 8 minutes. After the pre-sputtering process, the voltage and current of the B target are stabilized, and the rotation speed of the sample turntable is controlled at 3r / min. The voltage and current of the B target are adjusted to achieve a power of 140W, and sputtering is continued for 130 minutes to form an anti-scaling alloy film on the upper and lower surfaces of the Cr film.

[0113] Example 2

[0114] The mass ratio of each component in the anti-scaling alloy target is: Cu: 1300, Zn: 420, Ni: 240, Sn: 40, Cr: 100, Fe: 1, Si: 6. The other structural and methodological aspects of Example 2 are the same as in Example 1.

[0115] Example 3

[0116] The mass ratio of each component in the anti-scaling alloy target is: Cu: 1200, Zn: 300, Ni: 350, Sn: 50, Cr: 90, Fe: 10, Si: 8. The other structural and methodological aspects of Example 3 are the same as in Example 1.

[0117] Experimental performance analysis:

[0118] Experiment 1

[0119] The scale prevention performance of the scale-inhibiting alloy sheet in Example 1 was measured using a simulated circulating water experiment.

[0120] Step 1: Before the experiment, clean the circulating water treatment system with tap water and distilled water respectively, and use a brush to remove the scale on the circulating water treatment system to avoid residual scale affecting the experimental results.

[0121] Step 2: Prepare a hard water solution using 50 liters of deionized water, 24.37 g of calcium chloride dihydrate, 14.35 g of magnesium sulfate heptahydrate, and 25.16 g of sodium bicarbonate.

[0122] Step 3: Prepare six stainless steel hanging plates and record their weight. Hang them in the water tank of the water treatment system and ensure that all six stainless steel hanging plates are completely immersed in the hard water solution.

[0123] Step 4: Install the four anti-scaling alloy sheets from Example 1 into the alloy film anti-scaling device of the present invention, install the alloy film anti-scaling device into the circulating water treatment system, add the prepared hard water solution into the water tank, start the circulation experiment, and record the time.

[0124] Step 5: Every twelve hours, remove one stainless steel plate and place it in an oven to dry. After drying, take a microscopic image of the stainless steel plate under a microscope and measure the Ca in the circulating water. 2+ Changes in ion concentration, pH, and the mass of the stainless steel hanging sheet;

[0125] Step 6: Repeat step 5 to determine the anti-scaling performance of the stainless steel hanging plate each time it is removed.

[0126] Experiment 2

[0127] The traditional anti-scaling alloy sheet (Cu = 62 wt%, Zn = 38 wt%) was measured using a simulated circulating water experiment:

[0128] Replace the anti-scaling alloy sheet in step 4 of Experiment 1 with a traditional anti-scaling alloy sheet; all other aspects remain the same as in Experiment 1.

[0129] like Figure 7 The figures show the scale morphology of stainless steel hanging plates after (a) 12h, (b) 24h, (c) 36h, (d) 48h, (e) 60h, and (f) 72h, obtained by testing with traditional anti-scaling alloy plates.

[0130] like Figure 8 The images show the scale morphology of the stainless steel hanging plate obtained from the anti-scaling alloy plate of Example 1 at (a) 12h, (b) 24h, (c) 36h, (d) 48h, (e) 60h, and (f) 72h. It can be seen that the amount of scale accumulation on the anti-scaling alloy plate of Example 1 is significantly less than that on the traditional anti-scaling alloy plate at the same time, and the density of the scale is also significantly less than that on the traditional anti-scaling alloy plate.

[0131] like Figure 9 As shown, it can be seen that the scale mass on the stainless steel plate of the traditional anti-scaling alloy sheet is about twice that of the stainless steel plate of the anti-scaling sheet in Example 1. A large amount of scale is deposited on the stainless steel plate, which affects the flow of simulated circulating water in the anti-scaling device, resulting in the anti-scaling effect of the anti-scaling alloy sheet being halved.

[0132] like Figure 10 As shown, the pH of the circulating aqueous solution treated with the conventional anti-scaling alloy sheet is lower than that of the circulating aqueous solution treated with the anti-scaling alloy sheet of Example 1.

[0133] like Figure 11 As shown, the Ca in the circulating aqueous solution treated with traditional anti-scaling alloy sheets...2+ Compared to the Ca in the circulating aqueous solution treated with the anti-scaling alloy sheet of Example 1 2+ Low concentration indicates a large amount of Ca in the solution. 2+ quilt The combined substances form CaCO3 and CaSO4 scale, which adheres to the surface of the scale-preventing alloy plates and the inner wall of the scale inhibitor, causing changes in the pH and Ca content of the circulating water solution. 2+ The concentration was significantly reduced; it is evident that the anti-scaling effect of the anti-scaling alloy sheet in Example 1 is significantly higher than that of the traditional anti-scaling alloy sheet.

[0134] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. An alloy film anti-scaling device with anti-scaling function, characterized in that, It includes at least two pipe joints connected in series (1), a front connector (2) connected to the front pipe joint, and a rear connector (3) connected to the rear pipe joint; the pipe joint includes a round pipe (11) and a first annular connecting plate (12) provided at both ends of the round pipe; both the front connector and the rear connector include a second annular connecting plate (21) and a connecting pipe (20) connected to the second annular connecting plate; an anti-scaling alloy sheet (4) is provided between adjacent first annular connecting plates, and an anti-scaling alloy sheet is provided between connected first annular connecting plates and second annular connecting plates; the anti-scaling alloy sheet is provided with a plurality of uniformly arranged through holes (41); the anti-scaling alloy sheet includes a round sheet made of stainless steel, a transition layer provided on the upper and lower surfaces of the round sheet, and a functional layer provided on the outer surface of the transition layer; the transition layer is a Cr film, and the functional layer is an anti-scaling alloy film.

2. The alloy film anti-scaling device with anti-scaling function according to claim 1, characterized in that, The anti-scaling alloy film is prepared by magnetron sputtering of an anti-scaling alloy target. The mass ratio of each component in the anti-scaling alloy target is as follows: Cu: 1000-1300, Zn: 240-420, Ni: 240-420, Sn: 40-60, Cr: 1-100, Fe: 1-20, Si: 6-10.

3. The alloy film anti-scaling device with anti-scaling function according to claim 1, characterized in that, The through hole is a stepped hole, with the diameter of the stepped hole decreasing from top to bottom, and the inner edge of the stepped hole is provided with a rounded corner (411).

4. The alloy film anti-scaling device with anti-scaling function according to claim 1, characterized in that, The first annular connecting plate and the second annular connecting plate are each provided with a number of corresponding bolt holes (121). The corresponding surfaces of adjacent first annular connecting plates are each provided with a first annular groove (122) for accommodating the sealing ring. The corresponding surfaces of the first annular connecting plate and the second annular connecting plate are each provided with a second annular groove (124).

5. A method for manufacturing an alloy thin-film anti-scaling device with anti-scaling function as described in claim 2, characterized in that, Including the magnetron sputtering step of the anti-scaling alloy sheet: Step 5-1: Place the pretreated disc into the sputtering chamber of the magnetron sputtering instrument, fix the disc on the sample stage of the magnetron sputtering instrument, and cover the lower surface of the disc with a mask. Step 5-2: Install the Cr target material onto target A, then evacuate the magnetron sputtering chamber and introduce argon gas to sputter a Cr film on the upper surface of the disc to form a Cr film. Step 5-3: Power off the magnetron sputtering instrument and stop the argon gas supply to allow the temperature inside the sputtering chamber to drop below 60℃-80℃; remove the Cr target and disc from the sputtering chamber. Step 5-4: Repeat steps 5-1 to 5-3, cover the upper surface of the wafer with a mask, and magnetron sputter the lower surface of the wafer; Step 5-5: Place the disc into the magnetron sputtering chamber, use a clamp to fix the heated substrate to the disc, install the anti-scaling alloy target onto the B target holder, cover the lower surface of the disc with the sputtered Cr film with a mask plate, sputter the anti-scaling alloy film on the upper surface of the disc with the sputtered Cr film, and remove the disc. Steps 5-6: Repeat steps 5-5, cover the upper surface of the disc with a mask, and magnetron sputter an anti-scaling alloy film onto the lower surface of the Cr film. Steps 5-7: Place the disc into the heating zone of the furnace tube in the vacuum tube furnace, install insulated furnace plugs at both ends of the furnace tube, and perform vacuum heat treatment to obtain the scale-resistant alloy disc.

6. The method for manufacturing the alloy thin-film anti-scaling device with anti-scaling function according to claim 5, characterized in that, It also includes the preparation steps of the anti-scaling alloy target material: Step 6-1, Smelting: Preheat the graphite crucible to 800±10℃ and hold for 30-45 minutes to remove moisture. Add Cu, Ni, Sn, Cr, Fe, and Si of the anti-scaling alloy target to the graphite crucible according to their mass ratios. Heat the inside of the graphite crucible to 1150℃-1180℃ to completely melt all components. Stir the melt in the graphite crucible electromagnetically for 30-45 minutes. Cool the melt to 1050℃-1080℃ and add zinc ingots to the melt according to the mass ratio of the anti-scaling alloy target. Melt the zinc ingots and stir the melt rapidly with a graphite rod for 10-20 minutes. Cover the melt with a composite flux to prevent surface oxidation. Hold the graphite crucible at 1080℃±10℃ and stir the melt electromagnetically for 8-12 minutes to ensure uniform distribution of the components of the anti-scaling alloy target, thus obtaining the anti-scaling alloy target melt. Step 6-2: Deoxidize and refine the molten anti-scaling alloy target material; Step 6-3, Pouring: Preheat the anti-scaling alloy target mold to 200℃, spray zinc oxide coating on the mold, heat the mold to 1060℃-1100℃, and pour the molten anti-scaling alloy target into the mold under argon protection to obtain the anti-scaling alloy target ingot. Step 6-4, Demolding: Cool the anti-scaling alloy target mold to 150℃-250℃ for demolding; Step 6-5: Homogenize the anti-scaling alloy target ingot through annealing. Step 6-6: Hot rolling the anti-scaling alloy target ingot; Steps 6-7 involve cold rolling the anti-scaling alloy target material; Steps 6-8, Surface treatment and target material processing: The cold-rolled anti-scaling alloy target material is surface-machined to a thickness of 4mm, so that the roughness grade of the upper and lower surfaces of the anti-scaling alloy target material reaches N5, thus obtaining the final anti-scaling alloy target material.

7. The method for manufacturing the alloy thin-film anti-scaling device with anti-scaling function according to claim 5, characterized in that, The sputtering parameters for magnetron sputtering of the anti-fouling alloy film are as follows: The sputtering chamber was evacuated to a vacuum of 1.0 × 10⁻⁶. -3 Below Pa, the substrate temperature of the sample turntable is raised to 250℃-300℃ through heat transfer from the heated substrate; the bias voltage is adjusted to 100V-120V, argon gas is introduced into the sputtering chamber, and the argon gas flow rate is controlled at 30sccm-40sccm to raise the gas pressure in the sputtering chamber to 0.5Pa-0.7Pa; the voltage of the B target is raised to 300V-400V to perform glow discharge, which ionizes the argon gas and generates argon ions. The argon ions bombard the anti-scaling alloy target, causing the anti-scaling alloy target to sputter; the working gas pressure in the sputtering chamber is adjusted to 0.2±0.1Pa, and pre-sputtering is performed for 5min-10min; after the pre-sputtering process, the voltage and current of the B target are stabilized, the rotation speed of the sample turntable is controlled at 2r / min-4r / min, the voltage and current of the B target are adjusted to achieve a power of 120W-150W, and sputtering is continued for 100min-150min to form an anti-scaling alloy film on the Cr film surface.

8. The method for manufacturing the alloy thin-film anti-scaling device with anti-scaling function according to claim 5, characterized in that, Step 5-5 includes the following specific steps: Place the disc into the heating zone of the vacuum tube furnace tube, and evacuate the furnace tube to a vacuum level of 1.3 × 10⁻⁶. - 3 For pressures below MPa, install insulated furnace plugs at both ends of the furnace tube; The temperature inside the vacuum tube furnace is raised to 600℃-800℃ and held for 0.5-2 hours, allowing the disc to cool with the vacuum tube furnace. Once the temperature inside the vacuum tube furnace is below 60℃, the scale-resistant alloy disc is removed.

9. The method for manufacturing an alloy thin-film anti-scaling device with anti-scaling function according to claim 5, 6, 7, or 8, characterized in that Cr The thickness of the membrane is 200nm-400nm, and the thickness of the anti-scaling alloy membrane is 1000nm-1200nm.